2022
DOI: 10.1002/cnm.3581
|View full text |Cite
|
Sign up to set email alerts
|

Wet surface wall model for latent heat exchange during evaporation

Abstract: Air conditioning is a dual heat and mass transfer process, and the human nasal cavity achieves this through the mucosal wall surface, which is supplied with an energy source through the sub-epithelial network of capillaries. Computational studies of air conditioning in the nasal cavity have included temperature and humidity, but most studies solved these flow parameters separately, and in some cases, a constant mucosal surface temperature was used. Recent developments demonstrated that both heat and mass trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Salati et al [30] reported that N95 respirator mask breathing leads to excessive carbon dioxide inhalation and reduced heat transfer in the human nose. Inthavong et al [31] also showed a cooling effect on nasal mucosa from the latent heat of evaporation. Facial temperature and discomfort in healthcare workers were studied by Lembo et al [32], Zhu et al [33,34], and Beonell et al [35]; all reported a significant increase in facial temperature, but the increasing magnitude varied with the mask type, length of wearing time, and the individual's physical activity.…”
Section: Introductionmentioning
confidence: 97%
“…Salati et al [30] reported that N95 respirator mask breathing leads to excessive carbon dioxide inhalation and reduced heat transfer in the human nose. Inthavong et al [31] also showed a cooling effect on nasal mucosa from the latent heat of evaporation. Facial temperature and discomfort in healthcare workers were studied by Lembo et al [32], Zhu et al [33,34], and Beonell et al [35]; all reported a significant increase in facial temperature, but the increasing magnitude varied with the mask type, length of wearing time, and the individual's physical activity.…”
Section: Introductionmentioning
confidence: 97%
“…Such as Lindemann et al and Pless et al, did not incorporate water vapor transport. 8, 9 Garcia et al investigated the nasal cavity heat and water vapor transport between control and pathological subjects by assuming both constant cavity surface temperature and relative humidity. 7 A two-lm theory was applied in simulating the heating of nasal cavity air by Kumahata et evaluated the effects of latent heat, while the water transfer model assumed fully saturated conditions at the wall of the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recently, a study by Inthavong et al applied a two-lm theory to both the heat and water model in simulating the nasal cavity air-conditioning over a limited number of subjects. 9 The nasal cycle, a natural physiological process, alternately decongests one side of the nasal cavity approximately every two hours, leading to anatomical variations that can affect air-conditioning e ciency. 10 Prior studies often utilized single geometric models per subject, based on the nasal anatomy at the time of imaging, although it has been shown considering the airway dynamics can make big difference in CFD predicted resutls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation